Cardiometabolic risk factors in social housing residents: a multi-site cross-sectional survey in older adults from Ontario, Canada - Agarwal, Gina; Lee, Janice; Keshavarz, Home; Angeles, Ric; Pirrie, Melissa; Marzanek, Francine; Brar, Jasdeep; Koester, Christie; Mahal, Guneet; Plishka, Mikayla; Popal, Sahar (PLoS One, 2024)
Objective: This study describes cardiometabolic diseases and related risk factors in vulnerable older adults residing in social housing, aiming to inform primary care initiatives to reduce health inequities. Associations between sociodemographic variables, modifiable risk factors (clinical and behavioural), health-related quality of life and self-reported cardiometabolic diseases were investigated. Design, setting, and participants: This was a cross-sectional study with an interviewer-administered questionnaire. Data was collected from residents aged 55 years and older residing in 30 social housing apartment buildings in five regions in Ontario, Canada. Outcome measures: The proportion of cardiometabolic diseases and modifiable risk factors (e.g., clinical, behavioural, health status) in this population was calculated. Results: Questionnaires were completed with 1065 residents: mean age 72.4 years (SD = 8.87), 77.3% were female, 87.2% were white; 48.2% had less than high school education; 22.70% self-reported cardiovascular disease (CVD), 10.54% diabetes, 59.12% hypertension, 43.59% high cholesterol. These proportions were higher than the general population. Greater age was associated with overweight, high cholesterol, high blood pressure and CVD. Poor health-related quality of life was associated with self-reported CVD and diabetes. Conclusions: Older adults residing in social housing in Ontario have higher proportion of cardiovascular disease and modifiable risk factors compared to the general population. This vulnerable population should be considered at high risk of cardiometabolic disease. Primary care interventions appropriate for this population should be implemented to reduce individual and societal burdens of cardiometabolic disease.
An infographic presenting the results of the following publication: "Cardiometabolic risk factors in social housing residents: A multi-site cross-sectional survey in older adults from Ontario, Canada"
Keywords: Cardiometabolic; Vulnerable Populations; Social Housing; Community Paramedicine; Family Medicine